Trade Deficit?: An Analysis of Trade News Source Coverage in Business Aggregators. Issue 3 (17th November 2021) - Tully, Tim
ABSTRACT: Trade journals and trade news sources are an invaluable source for business students, entrepreneurs, and job seekers, but there have not been any recent analyses to determine whether these sources are adequately represented in the aggregator databases used by Business Librarians. In this study, the researcher compiled a list of 768 quality trade news sources using the First Research industry reports from ABI/INFORM Collection and compared the full text coverage and the currency of coverage of these sources in Business Source Complete, ABI/INFORM Collection, Business Insights: Global, Nexis Uni, and Factiva using UlrichsWeb and institutional journal holdings records. This study identified whether there was full text coverage of these sources in additional aggregator products from EBSCO, ProQuest, Gale, and LexisNexis. Lastly, this study offers a few suggestions for increasing the discoverability of trade sources that are not available in these aggregator packages.